Metabolic prioritization of fish in hypoxic waters: an integrative modeling approach - Duskey, Elizabeth (Frontiers in Marine Science, 2023)
Marine hypoxia has had major consequences for both economically and ecologically critical fish species around the world. As hypoxic regions continue to grow in severity and extent, we must deepen our understanding of mechanisms driving population and community responses to major stressors. It has been shown that food availability and habitat use are the most critical components of impacts on individual fish leading to observed outcomes at higher levels of organization. However, differences within and among species in partitioning available energy for metabolic demands – or metabolic prioritization – in response to stressors are often ignored. Here, I use both a multispecies size spectrum model and a meta-analysis to explore evidence in favor of metabolic prioritization in a community of commercially important fish species in the Baltic Sea. Modeling results suggest that metabolic prioritization is an important component of the individual response to hypoxia, that it interacts with other components to produce realistic community dynamics, and that different species may prioritize differently. It is thus suggested that declines in feeding activity, assimilation efficiency, and successful reproduction – in addition to low food availability and changing habitat use – are all important drivers of the community response to hypoxia. Meta-analysis results also provide evidence that the dominant predator in the study system prioritizes among metabolic demands, and that these priorities may change as oxygen declines. Going forward, experiments and models should explore how differences in priorities within and among communities drive responses to environmental degradation. This will help management efforts to tailor recovery programs to the physiological needs of species within a given system.